Effect of fracture location on rate of conversion to open reduction and clinical outcomes in pediatric Gartland type III supracondylar humerus fractures - EROL, BÜLENT (My University, 2022)
BACKGROUND: Supracondylar humerus fractures are the most common form of elbow fracture in children and adolescents. At present, treatment planning is based on the Gartland classification. Reduction and percutaneous pinning are done for Gartland type III fractures. In cases where closed reduction is unsuccessful, the procedure is converted to open reduction. However, there is no consensus on which patients are more likely to require conversion to open reduction. The aim of this study was to investigate the effect of fracture location on the rate of conversion to open reduction and clinical outcomes. METHODS: A total of 112 patients who underwent early surgery for Gartland type III supracondylar humerus fracture between August 2011 and August 2017 were evaluated. The patients\" age, sex, facture location, post-operative loss of reduction, and complications were noted. The fractures were classified according to fracture level relative to isthmus (high level) or at/below the isthmus (low level). Closed reduction was initially preferred. Open reduction with percutaneous pinning was performed, when necessary. Flynn\"s criteria were used to evaluate elbow motion after treatment. RESULTS: Mean follow-up time was 39 months (16-62 months). The mean age of the patients was 6.4 +/- 2 years (1.4-12 years). Thirty-nine of the patients were female, 73 were male; 32 fractures were in the dominant arm, 80 were in the non-dominant arm. Ninety of the fractures were classified as high level (proximal) and 22 as low level (distal). Patients with low-level fractures were significantly younger (p0.05). CONCLUSION: The Gartland classification provides important guidance for the treatment of supracondylar humerus fractures, but may have limitations. Our results suggest that revising the classification by incorporating fracture location may be more beneficial for pre-operative planning.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Acil Tıp; Medicine; Health Sciences; Surgery Medicine Sciences; Emergency Medicine; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Emergency Medical Services; Closed reduction; Gartland type III; open reduction; supracondylar humerus fractures; PERIOPERATIVE COMPLICATIONS; INTERNAL-FIXATION; DELAYED TREATMENT; SURGICAL DELAY; CHILDREN; NEED; MANAGEMENT